Modern conflict and the senses
1 online resource (xxiii, 391 pages)
Keywords: "Modern Conflict and the Senses investigates the sensual worlds created by modern war, focusing on the sensorial responses embodied in and provoked by the materiality of conflict and its aftermath. The volume positions the industrialized nature of twentieth-century war as a unique cultural phenomenon, in possession of a material and psychological intensity that embodies the extremes of human behaviour, from total economic mobilization to the unbearable sadness of individual loss. Adopting a coherent and integrated hybrid approach to the complexities of modern conflict, the book considers issues of memory, identity, and emotion through wartime experiences of tangible sensations and bodily requirements. This comprehensive and interdisciplinary collection draws upon archaeology, anthropology, military and cultural history, art history, cultural geography, and museum and heritage studies in order to revitalize our understandings of the role of the senses in conflict"--Provided by publisher.